2019
DOI: 10.1038/s41565-019-0565-0
|View full text |Cite
|
Sign up to set email alerts
|

Determining the phase diagram of atomically thin layered antiferromagnet CrCl3

Abstract: Changes in the spin configuration of atomicallythin, magnetic van-der-Waals multilayers can cause drastic modifications in their optoelectronic properties.Conversely, the optoelectronic response of these systems provides information about the magnetic state, very difficult to obtain otherwise. Here we show that in CrCl 3 multilayers, the dependence of the tunnelling conductance on applied magnetic field (H), temperature (T ), and number of layers (N ) tracks the evolution of the magnetic state, enabling the ma… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

12
147
0
4

Year Published

2019
2019
2023
2023

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 138 publications
(163 citation statements)
references
References 57 publications
(77 reference statements)
12
147
0
4
Order By: Relevance
“…Single electron transistor spectroscopy has found both electron and hole masses to be about 0.4-0.6 0 40 . In a magneto-optical measurement study of the inter-Landau level transition 41 , the exciton was estimated to be around 0.27 to 0.31 0 . These results are consistent with the value reported in ab initio calculations 42,43 .…”
Section: Exciton Physics In Layered Hexagonal Transition Metal Dichalmentioning
confidence: 99%
“…Single electron transistor spectroscopy has found both electron and hole masses to be about 0.4-0.6 0 40 . In a magneto-optical measurement study of the inter-Landau level transition 41 , the exciton was estimated to be around 0.27 to 0.31 0 . These results are consistent with the value reported in ab initio calculations 42,43 .…”
Section: Exciton Physics In Layered Hexagonal Transition Metal Dichalmentioning
confidence: 99%
“…Moreover, spinvalley locking by the spin-orbit coupling [18] as well as the presence of the valley-contrasting π Berry phase [12] give rise to a unique ladder of spin-and valley-polarized LLs in TMD monolayers [19,20], the degeneracy of which is further lifted by the strong Zeeman effect [21,22]. Although the fingerprints of such LLs have been recently reported in several transport experiments [23][24][25][26][27][28], their optical signatures have been obtained only for the WSe 2 monolayer at high electron densities, where exciton binding is suppressed due to screening; in this limit, the optical excitation spectrum is similar to that of GaAs 2DES at moderate fields and shows band-to-band inter-LL transitions [29].…”
mentioning
confidence: 99%
“…An externally applied magnetic field in the Faraday geometry lifts the valley degeneracy, resulting in a so-called valley Zeeman splitting [1]. Therefore, the g-factors of the excitons can be measured using helicity-resolved spectroscopy under magnetic fields [6][7][8][9][10][11][12][13][14][15][16][17][18][19]. In multilayer and bulk TMDCs, it has been found that the spin orientation of the carriers is strongly coupled to the valleys within the individual layers ("spin-layer locking") [17,[19][20][21].…”
mentioning
confidence: 99%